Pendampingan Disain HACCP Plan untuk Peningkatan Mutu Keamanan Pangan Produk Usaha Kecil Pangan Bakery di Bogor - Erniyati Erniyati; Puspa Citra; Legis Tsaniyah; Hermawan Hermawan (Universitas Kristen Indonesia Toraja, 2024)
The bakery industry is a sector that continues to grow through the crisis period in 2021 when Indonesia managed to record the highest bread sales in the Southeast Asia region with total transactions reaching USD 18.7 billion. Mak MPOEQ cake house in Bogor is one of the small food industries that has continued to produce during the Covid 19 pandemic until now. Bakery products are sensitive to contamination so they can easily and potentially spread food safety hazards. An integrated system of control and quality management of manufactured products is required, which makes it possible to implement timely measures to prevent, identify and eliminate deficiencies and errors in production, to provide reliable information about the products produced to consumers. To date, a system based on the use of Hazard Analysis Critical Control Points (HACCP) principles has been able to overcome these food safety problems well. The design of the HACCP system at Mak MPOEQ's cake house has been implemented through a community service mentoring program for staff from FMIPA Pakuan University in the period April-December 2023. The coaching is carried out following the stages of implementing the HACCP system as stated in SNI CAC/RCP 1 of 2011 issued by National Standardization Agency. The basic requirements for HACCP itself have been prepared by partners since 2021. The results of the hazard analysis carried out on the MPOEG Mak Cake House production system found 7 significant hazards out of the 20 hazards evaluated. Next, using the Codex decision tree, 4 CPPs were determined from the 7 hazards, namely egg receiving, flour sifting, filing, and vla cooking. Based on these 4 CCPs, a HACCP Plan has been prepared which focuses control on cleanliness when receiving eggs, physical contamination when sifting flour, sanitary bacteria from worker cross-contamination, and temperature and cooking time. All controls are carried out per activity batch and verified periodically.